ULTRASTRUCTURAL CHANGES OF THE MESENTRIC LYMPH NODES OF CALVES EXPERIMENTALLY INFECTED WITH SALMONELLA TYPHIMURIUM - A.W., Yass,; F.G., Habasha, F.G.; s., Al-Sammarai, (The Iraqi Journal of Veterinary Medicine, 2022)
A systemic study was done on the pathogenesis of experimentally induced Salmonella typhimurium infection in calves. The present investigation was carried out on sixteen normal colostrum fed friesian calves, ranging in age from 3 to 6 weeks. The calves were divided into two equal groups. Group I inoculated orally with (1.5 x 10’’) Salmonella typhimurium and group IA served as control. • The early ultrastructural alteration in the mesenteric lymph nodes was the presence of many free Salmonella in localized vacuoles. The interaction between the host cells and phagocytized Salmonella was also observed.